ANALISIS ALOKASI DANA KEGIATAN PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN KUTAI TIMUR - -, Indra Rusmawati (EKONOMIA, 2014)
Regional Development Planning Board (BAPPEDA) East Kutai, has one of the functions of planning the development of the region of East Kutai Regency, which is guided by the Strategic Plan (the Plan) and the working plan (Work Plan) Government of East Kutai, so all SKPDs (regional work units ) in the planning of development activities each year must obtain the approval of BAPPEDA in order to synchronize the Work Plan Budget (RKA) on education with a strategic plan and working plan Kabupatan East Kutai. Formulation of the problem is the allocation of funds to the activities of the Regional Planning Board of East Kutai has been implemented effectively? Basic Financial Management Theories include, Understanding Financial Management, Understanding Public Sector Management, Budget, Understanding Effectiveness. Hypothesis allocation of funds to the activities of the Regional Planning Board of East Kutai Regency are being implemented effectively. Analysis tool uses effectiveness ratio according Permendagri No. 13 of 2006 which compares with Realization Plan multiplied by 100%. The analysis showed that the allocation of development funds BAPPEDA in 2013 with 56 program activities carried out in Section Secretary, Economic Affairs, Field Data Collection and Reporting, Division of Physical and Infrastructure, Social and Cultural Mental and Spiritual, a total budget of Rp 28,139,922,625 realized Rp remaining budget of Rp 23,243,026,038 4,896,896,587 in average percentage - average overall program teralisasi approximately 82.6%. Based on the analysis results, the authors provide some suggestions that should the Governing BAPPEDA East Kutai may approach the subordinate staff implementing the program, so as to further improve the performance, especially in the realization of any program implemented and Chairman of the East Kutai Regency BAPPEDA need to improve the skills of employees through the program - training programs conducted both internally and externally as well as the leadership of the district BAPPEDA. East Kutai should always work together to Staffs BAPPEDA environment so as to always maintain the achievements they have gained subs proposed ini.Hipotesis accepted, because the allocation of funds BAPPEDA activities are being implemented effectively.